Pituitary stalk changes on magnetic resonance imaging following pituitary adenoma resection using a transsphenoidal approach - Zhang, Huijian; Zhang, Shuai; Shang, Mingchao; Wang, Jiaxing; Wei, Liangfeng; Wang, Shousen (Frontiers in Neurology, 2023)
Objective We aimed to investigate the magnetic resonance imaging (MRI) findings and clinical significance of position and changes in morphology of the pituitary stalk following pituitary adenoma (PA) resection using a transsphenoidal approach. Methods We collected clinical and MRI data of 108 patients with PA after transsphenoidal surgery. Diameter, length, and coronal deviation of the pituitary stalk were measured pre-, post-, and mid-term post-operatively, to observe pituitary stalk morphology. Results Of 108 patients, 53 pituitary stalks were recognisable pre-operatively. The angle between the pituitary stalk and the median line was 7.22°-50.20° (average, 25.85°) in 22 patients with left-sided pituitary stalks and 5.32°-64.05° (average, 21.63°) in 20 patients with right-sided pituitary stalks. Of 42 patients with preoperative pituitary stalk deviation, 41 had an early postoperative recovery and 1 had increased deviation. In the mid-term postoperative period, 21 of 42 patients had pituitary stalks located centrally. In 53 patients, the pituitary stalk length was 1.41–11.74 mm (mean, 6.12 mm) pre-operatively, 3.61–11.63 mm (mean, 6.93 mm) in the early postoperative period, and 5.37–17.57 mm (mean, 8.83 mm) in the mid-term postoperative period. In the early postoperative period, 58 (53.70%) patients had posterior pituitary bright spots (PPBS) and 28 (25.92%) had diabetes insipidus (DI). Conclusion Pre-operatively, the pituitary stalk was compressed and thinned. Post-operatively, it could be stretched to a “normal state”, and its position showed a gradual centring trend. Post-operatively, the length of the pituitary stalk gradually increased. The PPBS in the early postoperative period negatively correlated with postoperative DI.